Topics in Kwa Syntax - Aboh, Enoch O.; Essegbey, James; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2010)
Edited by two leading experts on the languages of West Africa, this volume is the very first book to handle a range of topics in the syntax of Kwa, a branch of the Niger-Congo language family spoken by approximately 20 million people in Côte d Ivoire, Ghana, Togo, and Benin and in the extreme southwestern corner of Nigeria. Kwa includes a total of 45 related languages. The nine chapters each address a separate grammatical aspect of Kwa. These range from topics such as the verb phrase, argument structure, verb serialization and complex predicates, to discussions on tense, mood, and aspect and their relation to the structure of sentences. Also addressed are the structure of the noun phrase and the syntax of discourse particles. The studies in this volume demonstrate that Kwa languages offer a very rich empirical domain for linguistic theorizing. In this book, experts who are mostly native speakers present empirical data and show its theoretical relevance to comparative linguistics and comparative syntax. The book brings together a wealth of material and fresh insights and is a superb example of how empirical research feeds into typological and theoretical linguistics. As such, it is a gold mine to students and teachers of comparative syntax, as well as for anyone interested in studies on Niger Congo languages.
The Phonology Syntax Interface -- The Morphosyntax of the Noun Phrase -- General Properties of the Clause -- The Non-agreeing Subject Resumptive Pronoun in Yoruba -- Relative Clauses in Akan -- C-Type Negation Markers on the Right Edge -- Information Packaging Constructions in Kwa: Micro-variation and Typology -- Inherent Complement Verbs and the Basic Double Object Construction in Gbe -- The Empty Subject Construction: Verb Serialization in Baule.
Keywords: Linguistics; African Languages; Comparative linguistics; Grammar, Comparative and general -- Syntax; Linguistics; Comparative Linguistics; African Languages; Syntax